A Combinatorial Approach for Assessing the Magnetic Properties of High Entropy Alloys: Role of Cr in AlCoxCr1–xFeNi1 . Issue 8 (24th May 2017) - Borkar, Tushar; Chaudhary, Varun; Gwalani, Bharat; Choudhuri, Deep; Mikler, Calvin V.; Soni, Vishal; Alam, Talukder; V. Ramanujan, Raju; Banerjee, Rajarshi
Abstract : A combinatorial assessment of composition‐microstructure‐magnetic property relationships in magnetic high entropy AlCox Cr1‐x FeNi alloy (0 ≤ x ≤ 1) system has been carried out using compositionally graded alloys fabricated via laser additive manufacturing. At one end, the AlCoFeNi composition (x = 1) consisted of equiaxed B2 grains, exhibiting very early stages of phase separation (only compositional partitioning) into Ni–Al rich and Fe–Co rich regions within grains of the B2 phase. At the other extreme, the AlCrFeNi composition (x = 0) exhibited grains with pronounced spinodal decomposition, resulting in a B2 + bcc microstructure with the degree of spinodal decomposition progressively increasing with Cr content in these AlCox Cr1–x FeNi alloys. While the saturation magnetization (Ms ) monotonically increases six times from x = 0 to x = 1, the coercivity (Hc ) variation is non‐monotonic, increasing seven times from x = 0 to x = 0.4, and subsequently decreasing fourteen times from x = 0.4 to x = 1.0. The magnetic phase transition temperature (Tc ) for these alloys also increases monotonically with increasing Co content with a second phase transition exhibited in a certain range of compositions between x = 0.6 to x = 0.8. Such substantial changes in the magnetization behavior and properties of magnetic high entropy systems opens possibilities of tuning these alloys for specific soft or hard magnetic component applications. Abstract : Laser Engineered Net Shaping (LENS™) process is used for making a compositionally graded magnetic AlCo x Cr1– x FeNi HEA (0 ≤  x  ≤1). The size scale of phase separation wave, which is affected by the composition, critically affects the magnetic properties like saturation magnetization and coercivity.